Investigation on the Current Status of Functional Movement Screen (FMS) for Male Specialized Football Athletes in Colleges and Universities - Yanqing Wei (International Journal of Education and Humanities, 2026)
Football is a high-intensity competitive sport that requires complex coordination of the shoulders, torso, and lower limbs. Movements such as footwork, sprinting, turning, and jumping demand a high level of physical fitness, which often increases the risk of sports injuries. Functional Movement Screening (FMS) is used to assess the quality of basic movement patterns and predict injury risks, allowing coaches to adjust training plans and provide corrective exercises. However, the application of FMS among university-level specialized football athletes remains limited. This study aims to examine the overall and sub-score characteristics of FMS among male university football players and to explore the relationship between FMS results and sports injuries. The study involved 18 male physical education students from Lvliang University who participated in the Shanxi Province Campus Football League. Before testing, participants completed a questionnaire on training duration and injury history over the past year. Their movement quality was then evaluated using the FMS kit. The collected data were analyzed to determine score distribution and its correlation with injury occurrence. Results showed that the highest total FMS score was 17 and the lowest was 7, each achieved by one participant. Most participants (72.2%) scored between 11 and 14. Nine athletes scored below 14, indicating a high risk of injury. Sub-scores were mostly in the range of 1–2 points. The highest scores appeared in the deep squat test, while the lowest were found in trunk rotation stability, which requires advanced coordination. The study concludes that core stability, ankle flexibility, quadriceps and rectus femoris strength, pelvic stability, and lower-limb coordination need improvement. Regular corrective training and routine FMS assessments are recommended to reduce injury risks and enhance team performance